Authoritarian elites. (16th October 2018) - Newson, Adlai; Trebbi, Francesco
Abstract: We explore the role of ruling elites in autocratic regimes and provide an assessment of tools useful to clarify the structure of opaque political environments. We first showcase the importance of analyzing autocratic regimes as non‐unitary actors by discussing extant work on non‐democracies in sub‐Saharan Africa and China, where the prevailing view of winner‐take‐all contests can be clearly rejected. We show how specific biographical information about powerful cadres helps shed light upon the composition of the inner circles that empower autocrats. We further provide an application of these methods to the Democratic People's Republic of Korea (DPRK), one of the most personalistic, opaque and data‐poor political regimes in the world today. Employing information from DPRK state media on participants at official state events, we are able to trace the evolution and consolidation of Supreme Leader Kim Jong Un around the transition period following the death of his father, Kim Jong Il. The internal factional divisions of the DPRK are explored during and after this transition. Final general considerations for the future study of the political economy of development are presented. Résumé: Élites autoritaristes . Les auteurs explorent le rôle des élites dirigeantes dans des régimes autocratiques et fournissent une évaluation des outils utiles pour clarifier la structure des environnements politiques opaques. On montre l'importance d'analyser les régimes autocratiques en tant qu'acteurs non‐unitaires en examinant les travaux disponibles sur les non‐démocraties de l'Afrique subsaharienne et de la Chine, où l'approche dominante par concours où tout va au vainqueur doit clairement être rejetée. On montre comment des renseignements biographiques spécifiques sur les cadres puissants jettent de la lumière sur la composition des cercles du pouvoir de l'autocrate. On montre aussi comment ces méthodes peuvent être appliquées à la République populaire démocratique de Corée (RDPC) – un des régimes politiques les plus personnalisés, opaques, et mal documentés du monde aujourd'hui. À l'aide d'information en provenance des médias d'état de la RDPC sur les participants aux événements officiels d'état, on est en mesure de retracer l'évolution et la consolidation de la position du leader suprême Kim Jong‐un au moment de la période de transition qui a suivi la mort de son père, Kim Jong‐iI. Les divisions internes en factions de la RDPC sont scrutées durant et après cette transition. Finalement, on présente certaines considérations générales sur les futures études de l'économie politique du développement.